The Validation Of COVID-19 Information In The Pharmacoepidemiological Research Database of Spain's Public Health System Data by Vaccination Status. - Astasio, Oliver; Castillo-Cano, Belén; Sánchez Delgado, Beatriz; Riefolo, Fabio; Gini, Rosa; Martín-Merino, Elisa (Perspectives in Health Information Management)
Purpose To validate COVID-19 information records in The Pharmacoepidemiological Research Database for Public Health System (BIFAP) of Spain. Methods The recorded COVID-19 cases in primary care or positive test registries (gold-standard) were identified among vaccinated patients against COVID-19 infection and their matched unvaccinated controls, between December 2020 and October 2021. The sensitivity, specificity, positive (PPV) and negative (NPV) predictive values were estimated for primary care records. Results Among 21,702 patients with positive tests and 20,866 with recorded COVID-19 diagnoses, the sensitivity, specificity, PPV and NPV were, respectively, 79.98 percent, 99.95 percent, 80.24 percent, and 99.94 percent among vaccinated, and 78.67 percent, 99.96 percent, 84.51 percent and 99.94 percent among controls. Conclusions Primary care COVID-19 diagnosis recorded in BIFAP showed that sensitivity was similar and PPV was slightly lower among vaccinated than unvaccinated controls. Among the elderly, COVID-19 diagnosis was less recorded. These findings permit the design of informed algorithms for performing COVID-19-related studies.